Assessment of the health risk for people residing on the territory influenced by the vostochny cosmodrome under multi-factor and multi-environment exposure to chemicals - A.D. Polyakov; M.Yu. Kombarova; A.S. Radilov; L.A. Alikbaeva; I.S. Iakubova; A.V. Suvorova; O.G. Khurtsilava (Analiz Riska Zdorovʹû)
Rocket and space activities occupy an important place among modern sources of impact on the environment. Its results can manifest themselves in an area where a cosmodrome is located, adjacent territories, in areas where separated parts of a launch vehicle fall. This impact has certain specific features that create population health risks.